Complete chloroplast genome sequence of Passiflora miniata (Passifloraceae). Issue 2 (2nd April 2020) - Mou, Hai-Fei; Wu, Yan-Yan; Fu, Long-Fei; Zhang, Ying-Jun; Wen, Fang; Liu, Jie-Yun; Tian, Qing-Lan; Huang, Wei-Hua; Wei, Yi-Gang
Abstract: The complete chloroplast genome of Passiflora miniata Vanderpl. was reported in this study. The cp genome was 149, 573 bp in length including two inverted repeats (IRs) of 25, 012 bp, which were separated by LSC and SSC of 86, 070 bp and 13, 479 bp, respectively. The GC content was 37.1%. The genome encoded 106 functional genes, including 72 protein-coding genes, 30 tRNA genes, and four rRNA genes. The maximum likelihood phylogenetic tree indicated that P. miniata was recovered in the clade of subg. Passiflora and most related to P. vitifolia . This newly reported plastid genome will provide essential data for further study on the phylogeny and evolution of the genus and family.